Review: Pemanfaatan Tanaman sebagai Fitoterapi pada Diabetes Mellitus - Dewi, Ni Luh Kade Arman Anita; Prameswari, Putu Nimas Diyah; Cahyaningsih, Erna; Megawati, Fitria; Agustini, Ni Putu Dewi; Juliadi, Debby (Usadha, 2022)
Diabetes is a chronic disease that occurs due to high levels of sugar in the blood, this can occur when the pancreas does not produce enough insulin (a hormone that regulates blood sugar or glucose), or when the body cannot effectively use the insulin it produces. Management of DM patients can be carried out with non-pharmacological and pharmacological therapies. The method used in the journal review was to search for the keyword "diabetes mellitus herbal medicine" for clinical studies on plant-derived products for the treatment of diabetes mellitus. Search terms included “phytotherapy”, “phytochemicals”, “medicinal plant products”, “herbal medicine”, and “diabetes mellitus”. Involving plant-derived compounds and pigmentation as outcome measures were included. In this review article, 30 journals were collected from which the objectives and results of the research in the journal were obtained. The goal is as an alternative management treatment to control blood sugar levels. For some of the compounds we discuss, among others: Flavonoids, Allicin, Lectins, Alkaloids, Andrographolid, Curcumin, Cinnamaldehyde, peptides, Phenolics, Tannins.